MiRNA profiling of gastrointestinal stromal tumors by nextgeneration sequencing - Gyvyte, Ugne; Juzenas, Simonas; Salteniene, Violeta; Kupcinskas, Juozas; Poskiene, Lina; Kucinskas, Laimutis; Jarmalaite, Sonata; Stuopelyte, Kristina; Steponaitiene, Ruta; Hemmrich-Stanisak, Georg; Hübenthal, Matthias; Link, Alexander; et al. (Oncotarget, 2017)
Deregulation of miRNAs has been observed virtually in all major types of cancer, whereas the miRNA signature in GIST is not well characterized yet. In this study the first high-throughput miRNA profiling of 15 paired GIST and adjacent normal tissue samples was performed using small RNA-seq approach and differentially expressed miRNAs as well as isomiRNAs were defined. Highly significantly deregulated miRNAs were selected for validation by Taq-Man low-density array in replication group of 40 paired samples. Validated miRNAs were further subjected to enrichment analysis, which revealed significantly enriched KEGG pathways in the main GIST associated pathways. Further, we used an integrated analysis of miRNA-mRNA correlations for KIT and PDGFRA target genes and found a significant correlation between all of the enriched miRNAs and their target gene KIT. Results of the phenotype analysis showed miR-509-3p to be up-regulated in epithelioid and mixed cell types compared to spindle type, whereas miR-215-5p showed negative correlation with risk grade of GIST. These data reveal a detailed miRNA profile of GIST and highlight new candidates that may be important in the development of malignant disease.
CRIS-Team Scopus Importer:2025-10-13
Keywords: GIST; MicroRNA; MicroRNA profiling; Small RNA-seq